Drug provision and health technology assessment in France - V. V. Omelyanovskiy; A. V. Nikitina; V. A. Lemeshko; G. R. Khachatryan (IRBIS LLC, 2020)
The article presents the description of structural, organizational and methodological issues of health technology assessment (HTA) of French drugs as well as the state-reimbursable list of drugs. The HTA is conducted by an independent public body - French National Authority for Health (HAS). HAS evaluates medical products, procedures, services and technologies from a medical and economic points of view to make cost recovery decisions. HAS consists of two committees providing HTA: Transparency Committee and the Economic and Public Health Assessment Committee. Thus, the French HTA consists of two separate components within the same agency. The result of HAS evaluation of a drug is a conclusion on the level of clinical value and clinical added value, as well as the methodological quality of the studies and the size of the target patient population. Based on the evaluation results, HAS gives recommendations for the National Union of Health Insurance Funds, the Economic Committee for Healthcare Products and Ministry of Health and publishes its opinion on the HAS website. HAS decisions are of a recommendatory nature - the final decision whether to include the drug in reimbursement lists are made by the Ministry of Health and published in the Official Journal of French republic.